Assessment of family planning service utilization and associated factors among female students at Assosa university, Ethiopia - Yonas Gashaw; Chekol Alemu (Scientific Reports)
Abstract Family planning is vital for reproductive health, enabling individuals to space children and plan their family size. Despite its importance, many women, especially students, don’t use family planning services. In Ethiopia, where the total fertility rate is 4.6 children per woman and 22% of women have an unmet need for family planning, this study assesses the use of family planning services among female students at Assosa University in Northwest Ethiopia. An institutional-based cross-sectional study was conducted among 351 female students at Assosa University from March to May 2023. Participants were randomly selected using stratified sampling. Data on demographics, family planning knowledge, attitude, and practice were collected through a pre-tested online questionnaire via Google Docs. The questionnaire, adapted from existing scales, was pilot-tested among 10% of the students before the main survey. Data analysis was performed using SPSS version 26, employing descriptive statistics, chi-square tests, and logistic regression. Results were reported as odds ratios with 95% confidence intervals, with a p-value of less than 0.05 considered statistically significant. Of the 345 female students surveyed, 98.3% participated. Most were young (18–20), single Christians with positive views on family planning. About 57.1% used family planning services, and religious reasons (75.4%) were the primary reason for non-use. Factors influencing service use included awareness of contraceptive benefits (AOR = 0.005, 95% CI: 0.000-0.460), prior use (AOR = 0.31, 95% CI: 0.124–0.781), side effects from discontinuation (AOR = 0.221, 95% CI: 0.101–0.487), and future intention (AOR = 4.812, 95% CI: 1.528–15.15). The study emphasizes that enhancing and promoting family planning services for female students at Assosa University is vital for overcoming socio-cultural and religious barriers.